FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI UNTUK MELAKUKAN WHISTLEBLOWING INTERNAL (STUDI EMPIRIS PADA OPD KOTA PEKANBARU) - Tulus Setiawan; Azwir Nasir; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted at the Head of Regional Device Organization of Pekanbaru City, Head of Finance, and Treasurer who works in the Organization of Pekanbaru City Regional Devices. This research is included in quantitative research. The type of data used in this study is primary data is data derived from the next source in data collection techniques, sampling is done by purposive sampling method with sampling technique with certain considerations (Sugiyono, 2012: 392) with the respondents as many as 100 employees working in Organization of Pekanbaru City Local Area. These data were analyzed using multiple regression with SPSS Version 22. This study aims to determine the effect of Organizational Commitment, Professional Commitment, Ethical Considerations, Personal Cost and Reward of Intention to conduct Internal Whistleblowing. The main issues that will be explained by the researcher are as follows: To see how big influence between dependent variable with independent variable. The results of this study indicate that Organizational Commitment has an effect on Intention to do Internal Whistleblowing, Professional Commitment has an effect on Intention to do Internal Whistleblowing, Ethical Consideration influence Intention to Internal Whistleblowing, Personal Cost have an effect on Intention to Internal Whistleblowing and Reward Influence on Intention to do Internal Whistleblowing. So the conclusion of this research is that all hypothesis presented is acceptable.Keywords : Organizational Commitment, Professional Commitment, Ethical Considerations, Personal Cost, Reward and Intention to conduct Internal Whistleblowing.